Controversies and Perspectives in the Use of Postoperative Radiotherapy for Prostate Cancer - Alan Dal Pra (Frontiers Research Topics, 2018)
The use of radical prostatectomy in patients with high risk of recurrence has significantly increased during the past 10 years. Thus, adjuvant radiation as a part of multimodality treatment or salvage radiation at the evidence of prostate-specific antigen (PSA) progression represents mainstay curative-intent options for a great number of prostate cancer patients. Although, few randomized trials and many retrospective studies have been published, many uncertainties still mold the discussions on the best treatment management for men after prostatectomy. This research topic successfully intended to foster discussions on current controversies in the use of postoperative radiotherapy and to present novel perspectives for treatment optimization.